ANALISIS PENGGUNAAN MODEL WHOLE LANGUAGE TIPE READING ALOUD TERHADAP KEMAMPUAN MEMBACA PERMULAAN DI KELAS II SDN 94 SINGKAWANG - Mutia Dewi; Rosmaiyadi; Wasis Suprapto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe students' initial reading abilities using the Whole Language Reading Aloud model for class II students at SDN 94 Singkawang and to describe the implementation of the use of the Whole Language Reading Aloud model in Indonesian language learning in class II at SDN 94 Singkawang. The type of research is qualitative with descriptive methods. The subjects and objects in this research were the Indonesian language teacher as the subject, and all class II students at SDN 94 Singkawang, totaling 30 students, as the object. Data collection techniques are test, observation, interview and documentation techniques with data collection tools in the form of initial reading ability test sheets, observation sheets and interview sheets. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results of the research are: 1) the initial reading ability of class II students at SDN 94 Singkawang using the reading aloud method is in the good category, reaching a percentage of 80%. 2) the implementation of the use of the whole language reading aloud type model in Indonesian language learning in Class IIA SDN 94 Singkawang which is carried out with learning steps and is effective in improving Indonesian language learning activities, especially towards beginning reading abilities. Based on the research results, it was concluded that the use of the reading aloud method on students' initial reading abilities in Class IIA SDN 94 Singkawang was effective in improving Indonesian language learning activities, especially on initial reading abilities.